(x + 4)(x + 1)

x = -1 or -4

(x + 4)(x2 - x - 1)

-2x + 2 and -3x + 2

(5x + 4)(5x + 4)

5x + 3 - 4 + 4x = 9x -1

2x + 7 + 5x - 4 - x = (2x + 5x - x) + (7 - 4) = 6x + 3

If -4 + 5x = 6, 5x = 6 +4 = 10 or x = 2.

Divide all terms by 2 and it can then be factored to (2x+1)(5x+2)

The factorization of 25x2 + 40x + 16 is (5x+4)(5x+4).

4 + 5x = 1 5x = 1 - 4 5x = -3 x = -3/5 x = -0.6

It is 5x - 4

(5x + 6)(x + 4)

5x + 4 - 3x + 5 + 2x - 9 = 4x

The answer to the math problem of 5x plus 12 equals 93-4 is 77/5.

If you mean: x^2 +5x +4 then it is (x+4)(x+1) when factored

The factors of x2 + 5x + 4 would be (x + 1) and (x + 4)

5x + 4 = 10x - 5 10x - 5x = 4 + 5 5x = 9 x = 1.8

Since 5x + 20 is a multiple of x + 4, it is automatically the LCD of this problem.

(5x)^-4 = 1/(5x)^4 = 1/625x^4 or this can be stated as x^-4/625

2X2+5x-12 4+5x-12 -8+5x 5x-8

4(5x + 3) - 9 = 20x + 3

True. 3x^4 + 4x^3 - 3x^4 + 5x + 1 = 4x^3 + 5x + 1

It is 14x+4 simplified

Factored, that's 4(5x + 1)(5x + 1) or 4(5x + 1)2 If the whole thing equals zero, x = -1/5

2x + x + 4 +2x = x + 20 5x + 4 = x + 20 5x - x = 20 - 4 4x = 16 x = 4

-5x + y = -4 Add 5x to each side: y = 5x - 4 The graph is a straight line with slope=5 and y-intercept = -4 .

-4x +5x +4 =7 x + 4 = 7 x = 3

5x+3 = 3x+11 5x-3x = 11-3 2x = 8 x = 4

5x+3 = -17 5x = -17-3 5x = -20 x = -4

simplified it would equal: 24x to the third power - x to the second power - x to the sixth power - 34

8x - 4 = -7 + 5x 8x - 5x - 4 = -7 + 5x - 5x subtract 5x from both sides 3x - 4 + 4 = -7 + 4 add 4 to both sides 3x = -3 x = -3/3 = -1

5x(x^4+7x+4)

8x-4 = -7+5x 8x-5x = -7+4 3x = -3 x = -1

5x - 4 = 3x + 6 5x - 3x = 6 + 4 2x = 10 x = 5

5x + (4 - 4x) = 0 5x + 4 - 4x = 0 x + 4 = 0 Subtract 4 from each side: x = -4

10x + 2y + 8z - 5x + 4z - 4y = 10x - 5x + 2y - 4y + 8z + 4z = (10 - 5)x + (2 - 4)y + (8 + 4)z = 5x - 2y + 12z

If your equation is 5x-2=4x+4 Then this is how you solve it... 5x-2=4x+4 5x-2+2=4x+4+2 5x=4x+6 5x-4x=4x-4x+6 x=6 Your x=6

3x+4 = 5x-6 3x-5x = -6-4 -2x = -10 x = 5

5x + 2 = 22 5x = 22 - 2 5x = 20 5x/5 = 20/5 x=4

Subtract 5x from each side: x + 4 = 11 Subtract 4 from each side: x = 7. Job done.

5x2 + 20x = 0 5x(x + 4) = 0 x = 0 and -4

3x + 2x = 5x. 5x= (-4) X = (-4)/5 x= -0.8

2(3x + 4) + 5x - 2

x2-5x+4 = (x-1)(x-4) when factored

(5x+4)(9x+9) FOIL First (5x*9x=45x**2) Outside (5x*9=45x) Inside (4*9x=36x) Last (4*9=36) 45x**2+45x+36x+36 45x**2+81x+36 9(5x**2+9x+4x)

-4 5x + 2 = -18 0x + -2 = -2 ---------------- 5x + 0 = -20 5x / 5 = -20/5 x = -4

3x+5=4-2x+6 5x=4-1 5x=3 x=3/5